Recording studios as museums? Record producers’ perspectives on German rock studios and accounts of their heritage practice - Herbst, Jan-Peter (Popular music, 2021)
Recording studios are shrouded in mystery. Some have become sites of pilgrimage; other studios have been converted into heritage museums. These practices are driven by city authorities, commercial heritage institutions or music fans. This interview study gives a voice to an understudied group: record producers and studio owners as the people in charge of popular music creation. Three German rock and metal producers expressed their opinion on the usefulness of studio museums and explained their own heritage practices. Their insights demystify the ‘magical aura’ associated with recording studios, picturing these spaces as places of pressure and anxiety. Hardly convinced of the technologically deterministic ‘magical contamination’ of technical equipment, the producers see little sense in studios as museums. For them, the released record is what counts. To stay in touch with the community and to keep the memory of their work alive, they prefer to use social media.